PERSEPSI MASYARAKAT WOMBO TERHADAP PENETAPAN KAWASAN HUTAN PENDIDIKAN UNIVERSITAS TADULAKO - Agustina, Ewit; Umar, Syukur; Toknok, Bau (Jurnal Warta Rimba, 2019)
Perception is the process of a stimulus to organize observations in such a way that they can be returned through the sense organs. This study aims to determine public perception of the determination of educational forest areas. This study was conducted for three months, namely in February 2018-April 2018. Materials and tools used in this study were questionnaires, writing instruments, cameras, calculators, computers and data what is needed in this study consists of primary and secondary data and using descriptive methods. The results of the scale interval of community knowledge about educational forests obtained 104 results that are less aware of the existence of educational forests. For the results of the interval scale community understanding of the basis and purpose of the education forest shows that community understanding for the category of very understanding with the total score of 75 there are 15 people, the category of understanding with a score of 60 there are 15 people, the category of less understanding with a score of 9 there are 3 people, the category does not understand with a score of 2 there is 1 person and very do not understand with a score of 0 there is 1 person so that an interval scale of 146 is found that the public understands what is meant by the basis and purpose of an educational forest. The results of the scale of community perception interval on the determination of educational forest area obtained an interval scale of 17 people in the excellent category with a total score of 3, a good category of 20 people with a total score of 80, a less good category 6 with a total score of 18, a bad category 0 with a total score of 0 and category is not very good 1 with a total score of 1 so that the final scale obtained is 134, which means the community's perception of the determination of the education forest area has not yet had a negative impact.